The Role of Transformational Leadership in Driving Operational Innovation in Manufacturing Industry Environments - Desy Kumalasari (Journal of Collaborative Industrial Management (JCIM), 2026)
This study examines the role of transformational leadership in driving operational innovation within manufacturing industry environments. Despite the extensive quantitative literature linking transformational leadership to organizational outcomes, the mechanisms through which transformational leaders cultivate operational innovation encompassing process improvements, efficiency enhancements, and quality driven change remain insufficiently explored through interpretive methods. Employing a qualitative research design with a multiple case study approach, this study collected data through in depth interviews with 34 key informants including plant managers, production supervisors, process engineers, and frontline operators across diverse manufacturing contexts. Data were complemented by non participant observations and document analysis. Thematic analysis revealed five core mechanisms through which transformational leadership stimulates operational innovation: (1) vision articulation as an innovation catalyst; (2) psychological safety creation enabling process challenge; (3) mentoring networks accelerating skill diffusion; (4) institutionalized innovation championing; and (5) co creative resistance management. The study further develops a five stage Transformational Leadership Operational Innovation (TLOI) model that traces the pathway from leadership behavior to sustainable innovation culture. Findings contribute to the industrial management literature by foregrounding the relational and cultural dimensions of operational innovation that conventional productivity metrics overlook. The study concludes with strategic recommendations for leadership development programs in manufacturing organizations.